2015
DOI: 10.1088/0957-4484/26/16/165403
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free ZnSnO3/MWCNTs-based self-poled flexible hybrid nanogenerator for piezoelectric power generation

Abstract: A high-performance flexible piezoelectric hybrid nanogenerator (HNG) based on lead-free perovskite zinc stannate (ZnSnO3) nanocubes and polydimethylsiloxane (PDMS) composite with multiwall carbon nanotubes (MWCNTs) as supplement filling material is demonstrated. Even without any electrical poling treatment, the HNG possesses an open-circuit voltage of 40 V and a short-circuit current of 0.4 μA, respectively, under repeated human finger impact. It has been demonstrated that the output volume power density of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
107
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(113 citation statements)
references
References 36 publications
(39 reference statements)
5
107
1
Order By: Relevance
“…Recently, nanocomposite generators based on PDMS with a mixture of ZnSnO 3 have been reported [29,30]. Kim et al have reported on piezoelectric power generation based on high concentration ZnSnO 3 mixed into PDMS under high pressure [31].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nanocomposite generators based on PDMS with a mixture of ZnSnO 3 have been reported [29,30]. Kim et al have reported on piezoelectric power generation based on high concentration ZnSnO 3 mixed into PDMS under high pressure [31].…”
Section: Introductionmentioning
confidence: 99%
“…Besides this, a positive charge cloud and an electronegative pole of P(VDF‐HFP) behave like a noncentro‐symmetric Eu 3+ :P(VDF‐HFP) complex comprising electroactive phases that may exhibit enhanced piezoelectric response. Such an architecture is likely to improve dielectrics and high energy storage capability as well . In this work, we fabricated a piezoelectric nanogenerator (PNG) made of a hybrid Eu 3+ :P(VDF‐HFP) composite film that exhibits 5 V open circuit voltage and 0.35 μA short‐circuit current which is capable of lighting ten commercial LEDs instantly.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it has been presumed that these types of flexible optical devices are very promising for several applications such as for the development of self‐powered and energy harvesting optical systems, wireless remote sensing, smart skin, bio‐labels, and so forth . This approach is simple, cost‐effective, and can scale‐up fabrication of high‐performance PNG that can sense different types of perturbations from environmental sources such as vibration/pressure from walking, air flow, transportation vehicles, water flow, sound vibrations, respiration, motion from body fluids, heart pulse, eye motion, and so forth . In a single polymer film, we achieve multi‐functionality such as flexibility, light emitting capability, ferroelectricity, energy storage property, and piezoelectric response.…”
Section: Introductionmentioning
confidence: 99%
“…BTO/PVDF generated a voltage of 7.99 V with an output current of 1.01 mA, whereas the proposed exible hybrid lm exhibited improved electrical performance with values of up to $11.9 V and $1.35 mA, respectively, under the same force of 11 N. The durability and reproducibility of the hybrid PENG were also shown to be effective by performing stability testing. Alam et al (2015) improved the performance of a ZnSnO 3 / PDMS-based hybrid PENG with multiwalled carbon nanotubes (MWCNTs) as a supplementary lling material. 250 The electrical performance of the fabricated PENG was improved owing to the good distribution of ZnSnO 3 nanocubes, and it generated an open-circuit voltage of 40 V, a short-circuit current of 0.4 mA and a power density of 10.8 mW cm À3 without electrical poling.…”
mentioning
confidence: 99%
“…Alam et al (2015) improved the performance of a ZnSnO 3 / PDMS-based hybrid PENG with multiwalled carbon nanotubes (MWCNTs) as a supplementary lling material. 250 The electrical performance of the fabricated PENG was improved owing to the good distribution of ZnSnO 3 nanocubes, and it generated an open-circuit voltage of 40 V, a short-circuit current of 0.4 mA and a power density of 10.8 mW cm À3 without electrical poling.…”
mentioning
confidence: 99%